2017
DOI: 10.1111/apa.13850
|View full text |Cite
|
Sign up to set email alerts
|

Rigid catheters reduced duration of less invasive surfactant therapy procedures in manikins

Abstract: Only rigid or stylet-guided catheters required tracheal catheterisation times similar to those of endotracheal intubation and neonatologists found them easier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…We have earlier reported that this improvised MIST equivalent of the semirigid catheter technique (the prototype is the LISA catheter) is technically simpler to adapt in clinical practice [15]. This observation is in conformity with earlier reports from Europe [23][24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We have earlier reported that this improvised MIST equivalent of the semirigid catheter technique (the prototype is the LISA catheter) is technically simpler to adapt in clinical practice [15]. This observation is in conformity with earlier reports from Europe [23][24].…”
Section: Discussionsupporting
confidence: 88%
“…As LISA catheter may not be readily available in all units, we later performed an improvised MIST procedure using the smallest size ETT 2.0, whose inner diameter is equivalent to 8 Fr infant feeding tube and instilled surfactant directly from a syringe attached to the hub of the ETT. Infant feeding tubes are usually made of polyurethane material that is much more flexible and hence difficult to guide into the trachea in contradistinction to the poly vinyl chloride material that is in ETT [23][24]. We have earlier reported that this improvised MIST equivalent of the semirigid catheter technique (the prototype is the LISA catheter) is technically simpler to adapt in clinical practice [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Angiocath and the LISAcath have a number of similarities, many of the LISAcath features were specifically designed to facilitate and secure tracheal intubation. Another study investigated different devices used for LISA and found that more rigid catheters, such as the Angiocath, permitted faster laryngeal catheterisation than gastric tubes . In the same study, the subjective ease of use of rigid catheters was also reported to be better.…”
Section: Discussionmentioning
confidence: 90%
“…These include gastric tubes, angiography catheters and vascular catheters, such as the Angiocath (Becton, Dickinson and Company, New Jersey, USA), which was the vascular catheter used by Dargaville et al. in their Hobart method for LISA . However, at the time that method was developed, there was no tool available that had been specifically designed for LISA.…”
Section: Introductionmentioning
confidence: 99%
“…Semirigid vascular catheters are also preferred by Spanish doctors [10]. Based on a manikin study, semirigid or stylet-guided vs flexible catheters allow faster tracheal insertion and are perceived as easier to use, although they have not been compared in a randomized study [19].…”
Section: Plos Onementioning
confidence: 99%